The Prevalence and Risk Factors of Workplace Violence at a Psychiatric Hospital in The Gambia - Amadou D. Jallow; Twisuk Punpeng; Chaweewon Boonshuyar (Psychiatry International)
Purpose—This study aimed to provide a comprehensive report of workplace violence (WPV) at a psychiatric hospital in Gambia. Design/methodology/approach—A cross-sectional study involving self-administered questionnaires and an in-depth interview was conducted with 54 staff at the hospital and six senior managers of mental health treatment in Gambia. A descriptive statistical approach was applied to determine the prevalence, and a logistic regression approach was used to identify factors associated with violence at the hospital. The data from the in-depth interviews on WPV policies in Gambia were analysed thematically. Results—In the 12 months before the research, 55.6% of the respondents had been exposed to violence; of those, 46.3%, 27.8%, and 5.6% had experienced verbal abuse, physical assault, and sexual harassment, respectively. Inadequate staff, insufficient security measures, and insufficient medications were perceived by respondents as the causes of the violence. However, the level of professionalism, the kind of services provided by staff, and shift of work were strongly connected with violence. As a result of WPV, victims had injuries, posttraumatic stress disorder signs/symptoms, and work dissatisfaction. The interviewees also expressed concern about the lack of WPV polices and the necessity of creating such polices as soon as possible. Value—According to the research, there is an elevated risk of violence among the hospital staff. As a result, the hospital’s structure needs to change, staff members should receive training on how to address aggressive patients, and a constructive WPV policy should be created.